2006
DOI: 10.1016/j.ecss.2006.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Availability, usage and expected contribution of potential nursery habitats for the California halibut

Abstract: Coastal ecosystems have been identified as important nursery habitats for many of the world's fishery species. Beyond this, there remain many questions about what exactly constitutes high-value, even critical, habitat for juvenile fish. A first step in investigating nursery habitat value should be to catalogue the spatial coverage (availability) of all potential nursery habitats as well as the distribution (usage) of juvenile fish within those habitats. We conducted two years of fall surveys in the nearshore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…Juvenile California Halibut are thought to use seasonally warm, prey-abundant estuaries to maximize their growth and survival before recruiting to adult stocks (Allen et al 2006;Fodrie and Mendoza 2006;Fodrie and Levin 2008). Halibut typically reach reproductive maturity at 59 cm for females and 32 cm for males, which means that the majority of the fish in our study were likely juveniles (Love and Brooks 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juvenile California Halibut are thought to use seasonally warm, prey-abundant estuaries to maximize their growth and survival before recruiting to adult stocks (Allen et al 2006;Fodrie and Mendoza 2006;Fodrie and Levin 2008). Halibut typically reach reproductive maturity at 59 cm for females and 32 cm for males, which means that the majority of the fish in our study were likely juveniles (Love and Brooks 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Because microhabitat conditions (submerged aquatic vegetation, intertidal mudflats, and emergent vegetation) allow estuaries to host juvenile fish at higher densities and increase their feeding and growth potential per unit area, these habitats are better suited to support specific fishery stocks than are exposed coastlines (Irlandi and Crawford 1997;Allen et al 2006;Fodrie and Mendoza 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Halibut recruit to estuaries at 10 to 70 mm standard length (SL) and begin to emigrate at around 140 mm SL (Kramer 1991). In smaller embayments (< 0.25 km 2 ), abundance is highest near the mouth, while in larger systems (> 0.25 km 2 ), it tends to be highest toward the middle or inner reaches (Fodrie & Mendoza 2006, López-Rasgado 2006. Kramer (1991) found that juvenile halibut within embayments tend to move deeper with age, regardless of distance from the embayment mouth.…”
Section: Methodsmentioning
confidence: 99%
“…we chemically defined all potential nurseries). North and south of our Baja sites, the coastline is rocky, highly exposed and unsuitable for juvenile halibut (Fodrie & Mendoza 2006). Also, a recent year-long survey found that the nearest sandy shoreline in the region (ca.…”
Section: Sdb Covers Over 45 Kmmentioning
confidence: 99%